Review paper Skin surface lipids and their measurements - Wójcik, Aneta; Budzisz, Elżbieta; Rotsztejn, Helena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
The lipid coat is the most external protective layer for the skin and hair. Improper functioning of sebaceous glands results in excessive oiliness and dryness of the skin as it is sebocytes that are the main source of lipid substances of sebum, secretion of the sebaceous glands, which is a mixture of lipids such as glycerides, free fatty acids, squalene, wax esters, cholesterol esters and cholesterol. In the past, a lot of methods were used to evaluate the skin lipids and measure their level. At present, a sebumeter and other measuring devices which objectively help to assess the level of skin oiliness are gaining more and more interest. The aim of the study is to present the current knowledge of the skin lipid coat and methods of measuring it.